THE ROLE OF INVESTMENT IN THE DEVELOPMENT OF INNOVATIVE TECHNOLOGIES: UZBEKISTAN'S EXPERIENCE AND INTERNATIONAL PRACTICE - Yusufjonov Ravshanbek Rustamjon ugli (The Conference Hub, 2025)
In the context of the rapid development of the global economy and increased competitiveness, the development of innovative technologies is central to the economic growth strategy of any country. By introducing modern technologies and developing innovative solutions, it is possible to increase production efficiency, create new products and services, and strengthen competitive positions in international markets. At the same time, investments play a very important role in the process of innovative development, as they allow financing research and development, technological innovations, and startups.